Unidirectional endotaxial cobalt di-silicide nanowires on Si(110) substrates. (25th September 2017) - Mahato, J C; Das, Debolina; Banu, Nasrin; Satpati, Biswarup; Dev, B N
Abstract: Self-organized growth of well-ordered endotaxial silicide nanowires (NWs) on clean Si(110) surfaces has been investigated by in situ scanning tunneling microscopy (STM) and transmission electron microscopy (TEM). Co deposition on clean Si(110) reconstructed surfaces at ∼600 °C produces unidirectional CoSi2 NWs by reaction of cobalt with the hot silicon substrate. STM investigations reveal four major types of distinct NWs, all growing along the [-110] in-plane direction except one type growing along the in-plane [-113] direction. There are also some nanodots. The cross-sectional TEM measurements show that the unidirectional NWs are of two types—flat-top and ridged. The NWs grow not only on the substrate but also into the substrate. CoSi2 in flat top NWs are in the same crystallographic orientation as the substrate Si and the buried interfaces between CoSi2 and Si are A-type. In the ridged NWs CoSi2 and Si are in different crystallographic orientations and the interfaces are B-type. The ridged NWs are in general wider and grow deeper into the substrate.